2010
DOI: 10.1159/000318522
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience with the Active Middle Ear Implant Vibrant Soundbridge in Sensorineural Hearing Loss

Abstract: The AMEI system VSB can be considered as an effective rehabilitation alternative in subjects with mild-to-severe SNHL and unsatisfying benefit from conventional hearing aids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
3
8
0
Order By: Relevance
“…Mean FHG values were satisfactory in patients with types of hearing loss. The mean FHG for sensorineural hearing loss is in accordance with the literature ranging from 13.9 to 28.1 dB on average . Two studies reported higher mean hearing gains in patients with conductive and mixed hearing loss (32 dB and 36.1 dB).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Mean FHG values were satisfactory in patients with types of hearing loss. The mean FHG for sensorineural hearing loss is in accordance with the literature ranging from 13.9 to 28.1 dB on average . Two studies reported higher mean hearing gains in patients with conductive and mixed hearing loss (32 dB and 36.1 dB).…”
Section: Discussionsupporting
confidence: 88%
“…The mean FHG for sensorineural hearing loss is in accordance with the literature ranging from 13.9 to 28.1 dB on average. [15][16][17][18] Two studies reported higher mean hearing gains in patients with conductive and mixed hearing loss (32 dB 19 and 36.1 dB 20 ). When analyzed by each frequency, significant hearing gains were reached at each frequency from 500 to 4,000 Hz.…”
Section: Discussionmentioning
confidence: 99%
“…The AC threshold of 1-8 kHz reached the normal hearing threshold level (<25 dB). In summary, a high frequency achieved a better effect than a lower frequency, which was consistent with a previous report [14]. The effect of hearing improvement in the high-frequency region (1-8 kHz) was better than the effect of our previously reported stapes implantation and round window implantation.…”
Section: Discussionsupporting
confidence: 92%
“…VSB-aided speech audiometry in quiet (Freiburger monosyllables speech test at 65 dB SPL) showed with 85% (Patient 1) and 80% (Patient 2) higher speech discrimination scores with the SP2 coupler than that in previous studies with application of the FMT to the long incus process, where speech discrimination was variously reported to be 57% to 61% (20,30) or 73% to 75% (31). Clearly, long-term results and a larger number of patients using this technique are required.…”
Section: Clinical Datamentioning
confidence: 65%